Earth observation micro-satellite design optimization using satellite simulator / Robertus Heru Triharjanto ... [et al.] - Heru Triharjanto, Robertus (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
With the more demanding performances and more limited resources available, obtaining an optimized engineering design is the necesity for design engineers. Therefore, the objective of the research is to develop method for optimizing satellite design. The satellite design phase concerned in the research is in detail design, which mean that the choices for basic configurations of the satellite has been determined. The design case is Earth observation microsatellite, with objective of the optimization is the minimum power consumption from the attitude control subsystem. Doing so, the payload duty cycle, and therefore, the image coverage can be increased. In order to perform the optimization that involve attitude control subsystem, a high-fidelity modeling tool, which in this context means the attitude dynamics module of the satellite simulator used. The module calculate the satellite orientation at any time, and the torque required to perform the camera pointing operation, which is the base for power consumption calculation. The result shows that the simulator can support the selection of the satellite optimal configuration by providing evidence of minimum power consumption. It is also find that due to full acces level, the self-made simulator as used in the research has good potential to be used in the optimization case with search algorithm.